Object detection for automatic cancer cell counting in zebrafish xenografts - Albuquerque, Carina (2021)
Albuquerque, C., Vanneschi, L., Henriques, R., Castelli, M., Póvoa, V., Fior, R., & Papanikolaou, N. (2021). Object detection for automatic cancer cell counting in zebrafish xenografts. PLoS ONE, 16(11), 1-28. [e0260609]. https://doi.org/10.1371/journal.pone.0260609 -----------------------------------------This work was supported by national funds through FCT (Fundaçâo para a Ciência e a Tecnologia), under project PTDC/CCI-INF/29168/2017 (BINDER). Mauro Castelli acknowledges the financial support from the Slovenian Research Agency (research core funding no. P5-0410).